Influence of soil anisotropic stiffness on the deformation induced by an open pit excavation - Katarzyna Lisewska; Marcin Cudny (Archives of Civil Engineering, 2023)
In this paper, the problem of deformation induced by an open pit excavation in anisotropic stiff soils is analysed by FE modelling. The presented research is focused on the influence of material model with anisotropic stiffness on the accuracy of deformation predictions as compared with the field measurements. A new hyperelastic-plastic model is applied to simulate anisotropic mechanical behaviour of stiff soils. It is capable to reproduce mixed variable stress-induced anisotropy and constant inherent cross-anisotropy of the small strain stiffness. The degradation of stiffness depending on strain is modelled with the Brick-type model. The model formulation and parameters are briefly presented. General deformation pattern obtained in the exemplary 2D boundary value problem of an open pit excavation is investigated considering different values of inherent cross-anisotropy coefficient of small strain stiffness. The numerical simulations are performed as a coupled deformation-flow analysis which allows to properly model the drainage conditions. The excavation phases are simulated by removal of soil layers according to the realistic time schedule. Finally, the monitored case of the trial open pit excavation in heavily overconsolidated Oxford Clay at Elstow, UK is simulated with proposed material model both in 2D and 3D conditions. The obtained calculation results are compared with displacement measurements and discussed.